Will Employer Branding Through Exploring Dynamics Between Organizational Learning, Organizational Culture and Employee Wellbeing? - Anita Maharani; Andi Maulana; Dovi Kurniawan; Yozef Yozef (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This study aimed to see how well-formulated organizational learning, organizational culture, and employee well-being impact better employer branding. The literature used to help build this research model is through concepts related to the four aforementioned variables. Design/methodology/approach: This study uses a quantitative research approach, distributing surveys for data collection and conducting analysis with a structural model approach Findings: The results obtained from this study are that employer branding is driven by organizational culture and employee well-being, while organizational learning does not affect it. Research limitations/implications: This research need more exploration due to the research object Practical implications: The implication of this research may show insights from employee’s perspectives on employer branding. Originality/value: This paper was conducted based on research of organizational learning, organizational culture, and employer branding Paper type: Research paper